Identifikasi dan Penentuan Jenis Cendawan yang Menginfeksi Kulit Pasien Balita di Rumah Sakit Umum Pusat Haji Adam Malik Medan - Ratnawati ratnawati; E. Harso Kardhinata; Sartini sartini (Universitas Medan Area, 2017)
This study aims to identify the types of fungi that infect skin toddler patients at the General Hospital Haji Adam Malik Medan. The study was conducted by descriptive method using examination observation fungi on skin scrapingssuffering from infection with a total of 30 samples. Examination was performed using 10% KOH and fungal culture media Sabouraud Dextrose Agar and incubated at room temperature (25-30oC). Based on the results of this study concluded that the type of fungus that infects the skin of patients under five years old are Trichophytonrubrum, Microsporummgypseum, Epidermiophytonfloccosum, Candida albicans and Candida tropicalis.